Effectiveness of the integration of traditional Chinese medicine and western medicine (integrative medicine) for treating liver stagnation and spleen deficiency in major depressive disorder: a randomized controlled trial protocol - Yao Song Han; Jo Anne Saw; JiangWei Yu; Xin Wee Chen (Cogent Psychology, 2024)
Objective Increasing number of depression cases, drug tolerability and compliance issues have triggered researchers to actively seek potential alternative treatment modalities. Integrating traditional Chinese medicine (TCM) and Western medicine (integrative medicine) has demonstrated favourable treatment outcomes for depression. However, most studies have focused on single-modality of TCM therapy, and its sustainability has rarely been evaluated. This protocol aims to describe a trial investigating the multi-modality integrative medicine effectiveness while measuring the post-intervention effect sustainability in treating liver stagnation and spleen deficiency in major depressive disorder (MDD).Methods/design A total of 318 eligible patients meeting the International Statistical Classification of Disease 10th Edition criteria for MDD and diagnosed with liver stagnation and spleen deficiency will be randomly allocated to receive Western medicine (Group A), Western medicine plus single-modality non-invasive TCM (Group B) or Western medicine plus comprehensive TCM (Group C). Each patient will receive a 6-week treatment; primary outcomes measured will be the overall response rate, changes in both Hamilton Depression Rating Scale 24 and Treatment Emergent Symptom Scale scores 18 weeks after randomisation. The secondary outcomes will include scores on the Pittsburgh Sleep Quality Index, Beck Depression Inventory-II, Health-related Quality of Life scale and Family Burden Scale 0, 3, 6, 10 and 18 weeks post-randomisation. Intention-to-treat analysis will be conducted using repeated-measures analysis of variance and covariance.Discussion Because there are various manifestations of MDD from the perspective of TCM, this trial may recommend a customised evidence-based regimen with longer potency for treating liver stagnation and spleen deficiency in MDD.